Challenges to critical infrastructure resilience in an institutionally fragmented setting. (December 2018) - Cedergren, Alexander; Johansson, Jonas; Hassel, Henrik
Highlights: Many Critical Infrastructures have been institutionally fragmented. Challenges to critical infrastructure resilience in such setting is explored. Response and recovery after failures is often complicated and time-consuming. The importance of contractual arrangements for shaping resilience is illustrated. Organisational resilience does not correlate with infrastructure resilience. Abstract: Under the influence of neo-liberal ideals such as New Public Management, the ownership, operation, and maintenance of many Critical Infrastructures have been divided among an increasing number of public as well as private actors. Limited research has investigated the role of this institutional fragmentation for shaping resilience of Critical Infrastructures, especially in relation to recovery after infrastructure failures. The aim of this paper is to empirically explore inter-organisational challenges to response and recovery operations in the increasingly multi-actor setting characterising many contemporary Critical Infrastructures. Using the Swedish railway system as a case, the paper explores response and recovery operations following two frequent types of events. The findings show that once disruptions occur, response and recovery operations are often complicated and time-consuming. Multiple actors with diverse roles and mandates are involved in the operations, which prompts a need for communication and coordination. The case study also illustrates the important role of contractual arrangements for shaping resilience of deregulated Critical Infrastructures. The contracts incentivise actors to certain behaviours, but they also give rise to unintended side-effects. While individual actors typically make adaptations and goal trade-offs with regards to their individual tasks and actions in a way that is both locally rational and efficient, interconnections and interdependencies among the different actors give rise to cross-scale challenges to stimulating resilient operations of the infrastructure system as a whole.